SURGICAL MANAGEMENT OF FRACTURE BOTH BONES FOREARM WITH LOCKING COMPRESSION PLATE IN ADULT PATIENTS - BHARGHAVA VEM, KRISHNA; KUMAR CHALLA, SHIVA; MURTHY D, SRINIVAS (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to assess the time taken for surgery, tourniquet time, and clinical outcome in diaphyseal fractures of both forearms managed with locking compression plate (LCP). Methods: Patients underwent open reduction and internal fixation with 3.5-mm LCP. Proximal radius was approached by dorsal Thompson incision and middle and distal radius by volar henry approach. A minimum of 6 cortices were engaged with screw fixation in each fragment. Ulna was approached directly over the subcutaneous border. Results: Of 20 patients, 70% were men; fracture was the most common in second and third decades of life. Road traffic accident (50%) and fall (40%) were the main causes. Fractures at mid-diaphysis (70%) and transverse/short oblique (72.5%) were the most common. Closed head injury, unilateral pubic bone fracture, olecranon fracture, fracture of both bones of leg, and ipsilateral fracture shaft humerus were the associated injuries. There was no intraoperative complication. Superficial infection (n=01) and transient posterior interosseous nerve injury, in the immediate postoperative period (n=01), were the reported complications. Average time for surgery was 77 min (60–90 min) and that for tourniquet was 54 min (40–60 min). All had complete union in <6 months; 80% had healing in <4 months. 20% healed in 4–6 months. Excellent and satisfactory results were seen in 85% and 15% patients, respectively. Conclusion: The 3.5-mm LCP, when applied properly, yields excellent outcome in fractures of forearm bones. The use of tourniquet, separate incisions for radius and ulna, and preservation of the natural curves of radius will reduce complications. Clinical outcome in terms of healing and union is excellent.